Utilization of several nitrogen sources by photosynthetic bacteria isolated in Vietnam - To Uyen, Do Thi; Nhi, Tran Van; Dung, Nguyen Ngoc; Kleiner, Diethelm (Academia Journal of Biology, 2015)
Twelve strains of photosynthetic bacteria were cultivated on solid agar medium in absence or presence of NH4+ or NO3- under nitrogen air condition. Their nitrogenase activity after 24h of cultivation in liquid medium containing these components was determinated. The activity of the GOGAT, GS and GluDH enzymes and the NH4+-transport system in cell-free extracts of all strains were found. The nitrogenase activity, biomass accumulation and NH4+ concentration were followed during the growth of the strain T17. The obtained experimental results showed that all studied photosynthetic bacteria strains were capable to fix N2. Ammonium and nitrate could be used for the bacterial growth and inhibited nitrogenase at certain concentration.